2009
DOI: 10.1002/dat.20296
|View full text |Cite
|
Sign up to set email alerts
|

Determining Quality of Life and Sleep in Hemodialysis Patients

Abstract: BACKGROUNDHemodialysis causes major changes in patients' lifestyles that affect their quality of life (QoL) and sleep quality. The purpose of this study was to determine the quality of life and sleep of hemodialysis patients.METHODS AND MATERIALSThe study sample was 138 patients receiving dialysis in a university hospital dialysis unit. Data were collected with a personal information form (PIF), Medical Outcomes Study 36‐item Short Form (SF‐36) questionnaire, and the Pittsburg Sleep Quality Index (PSQI).RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 28 publications
6
17
1
Order By: Relevance
“…Although this association was also present in our cohort, a multivariate analysis failed to show age as an independent predictive factor. Our study revealed a significant difference in SQ by gender, which is consistent with previous data in the dialysis population [3] [10]. In fact, gender appears to be the single most important factor discerning between PS and GS in our cohort, an effect that was not obvious in previous investigations [9].…”
Section: Discussionsupporting
confidence: 92%
“…Although this association was also present in our cohort, a multivariate analysis failed to show age as an independent predictive factor. Our study revealed a significant difference in SQ by gender, which is consistent with previous data in the dialysis population [3] [10]. In fact, gender appears to be the single most important factor discerning between PS and GS in our cohort, an effect that was not obvious in previous investigations [9].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, increased duration of disease, other accompanying diseases, and aging could cause changes in the quality of life. Some studies indicated no significant relationship between the duration of hemodialysis and quality of life (19,22,25,26). Also, Anees et al revealed that duration of hemodialysis was inversely correlated with quality of life (27).…”
Section: Discussionmentioning
confidence: 99%
“…Support by spouses can be a source of strength whereas support from friends is significant to retired hemodialysis individuals (19). However, it is intriguing to ascertain the critical role of family since living within an extended family is associated with poor quality of life (30). Equally important, is the support provided by health care professionals since it improves the way hemodialysis patients perceive their health (31).…”
Section: Discussionmentioning
confidence: 99%